Control of Slippery Conditions on Mining Roads Through Layering with Crusher Reject Material on the Hauling Road from Pit to Rom Pit Basalt PPA During Q4 2025 - Deni Prasetio; Haryadi Indriyanto; Kurnia Subandana; Mario Andrean Nurhadi Wicaksana; Andi Yogo Pramono (Journal of Social Research, 2026)
The slippery condition of the mining road on the Pit to ROM Pit Basalt PPA hauling line is one of the main obstacles to achieving production targets and ensuring work safety. During the January–June 2025 period, the year-to-date slippery value on the Pit to ROM road exceeded the company's standard threshold, reaching an average of 243% or 1.83 hours per rainy event. This high value resulted from limitations in hard materials for road layering, soil conditions prone to slipperiness, suboptimal road geometry, and inadequate drainage systems. The impacts included decreased effective working hours for transportation equipment, increased unsafe conditions, and lost revenue from basalt loading activities. This study aims to evaluate the effectiveness of crusher reject material as an alternative for road layering to control slippery conditions in the Pit to ROM hauling area. It is an applied improvement study, problem-solving oriented, using the Quality Control Project (QCP) approach. The analysis employed quantitative and qualitative methods through before–after comparisons, supported by field observations and technical evaluations of the mining road conditions. The results show that layering with crusher reject material, supported by road geometry improvements and drainage normalization, significantly reduced slippery duration, increased effective working hours for hauler units, and generated revenue gains of Rp460,430,676. This study implies that crusher reject material offers an effective, safe, and economical technical solution for sustainable mining road management.